2005
DOI: 10.1103/physrevb.71.174424
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in two polymorphs of tetra-kis-(dimethylamino)-ethylene-C60: An x-ray diffraction study

Abstract: A type of low-temperature structure for ferromagnetic ␣-tetra-kis ͑dimethylamino͒-ethylene ͑TDAE͒-C 60 is proposed on the basis of low-temperature x-ray analysis. We observed that intense superlattice reflections with odd indices successively appeared below T s = 170 K. The space group symmetry of the low-temperature phase is determined to be P2 1 / n. Two inequivalent C 60 sites exist in the low-temperature phase, which are indispensable to the orbital ordering model of C 60 . The contact configuration for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In the case of the ferromagnet TDAE-C 60 , the cages reside at sites of inversion ͑C i ͒ symmetry and the system is ordered at low temperature. 20 Thus our present results suggest that the C 60 − anion would have a C i -distorted equilibrium configuration in this material. In fact, since our simulated C i distortion has an elongation axis through opposing five-membered rings, it agrees with the proposed antiferro-rotative structure of Fig.…”
Section: Geometry Of C 2h5 -Distorted C 60 −mentioning
confidence: 81%
See 1 more Smart Citation
“…In the case of the ferromagnet TDAE-C 60 , the cages reside at sites of inversion ͑C i ͒ symmetry and the system is ordered at low temperature. 20 Thus our present results suggest that the C 60 − anion would have a C i -distorted equilibrium configuration in this material. In fact, since our simulated C i distortion has an elongation axis through opposing five-membered rings, it agrees with the proposed antiferro-rotative structure of Fig.…”
Section: Geometry Of C 2h5 -Distorted C 60 −mentioning
confidence: 81%
“…[11][12][13][14][15][16][17] Although cooperative effects among JT-distorted C 60 anions are assumed to play a crucial role in the properties of these materials, evidence of the actual distortion is usually indirect and often ambiguous. 18 Nuclear magnetic resonance ͑NMR͒ data of TDAE-C 60 indicate a beltlike distribution of the electron density associated with a Jahn-Teller elongation of the cage, 19 and the contact configuration between neighboring cages appears to be crucial, 20 but the actual distortion symmetry of the cage has not been experimentally determined. Among the A 4 C 60 compounds, only in Cs 4 C 60 , which makes a transition to a cooperative JT state at low temperature, was structural evidence found for a distortion of the cage ͑D 2h in this case͒.…”
Section: Introductionmentioning
confidence: 98%
“…CALC. by Fujiwara et al 30 . The average bond lengths of fullerite are taken from the results of neutron diffraction at 5K by David et al 31 and X-ray diffraction at 110K by Bürgi et al 32 To remove the thermal expansion of the C-C bond lengths, we use sets of bond lengths of C 60 and C − 60 which are measured at close temperature.…”
Section: Derivation Of the Vibronic Coupling Constants Of Ag Modesmentioning
confidence: 92%
“…Organic ferromagnets [91] and quantum Hall ferromagnets [92] demonstrate that ferromagnetism is possible in materials without magnetic ions, albeit the corresponding Curie temperatures are rather low, below 20 K. It has also been suggested that a robust ferromagnetism can appear in certain zinc-blende metals, such as CaAs, driven by a Stoner instability in the narrow heavy holes band [93]. There is, however, a number of qualitative indications against the persistence of ferromagnetism up to above room temperature in semiconductors, oxides, or carbon derivatives incorporating no magnetic elements and, at the same time, containing only a low carrier density, as witnessed by the high resistivity.…”
Section: Effects Of Competing Magnetic Interactionsmentioning
confidence: 99%